2013
DOI: 10.1186/1471-2164-14-725
|View full text |Cite
|
Sign up to set email alerts
|

Positively correlated miRNA-mRNA regulatory networks in mouse frontal cortex during early stages of alcohol dependence

Abstract: Background: Although the study of gene regulation via the action of specific microRNAs (miRNAs) has experienced a boom in recent years, the analysis of genome-wide interaction networks among miRNAs and respective targeted mRNAs has lagged behind. MicroRNAs simultaneously target many transcripts and fine-tune the expression of genes through cooperative/combinatorial targeting. Therefore, they have a large regulatory potential that could widely impact development and progression of diseases, as well as contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
113
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 78 publications
17
113
3
3
Order By: Relevance
“…Consistent with previous observations, miRNA-339-5p was found to be upregulated in mouse alcohol-induced brain damage [32]. We found that ethanol itself could induce miR-339-5p expression; meanwhile, Tβ4 treatment could induce a significant increase in miR-339-5p expression in BV2 cells exposed to ethanol.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with previous observations, miRNA-339-5p was found to be upregulated in mouse alcohol-induced brain damage [32]. We found that ethanol itself could induce miR-339-5p expression; meanwhile, Tβ4 treatment could induce a significant increase in miR-339-5p expression in BV2 cells exposed to ethanol.…”
Section: Discussionsupporting
confidence: 80%
“…We used a combination of unbiased methods to reveal key microRNAs and their targets. Chronic alcohol consumption caused robust changes in synaptic microRNA expression levels consistent with those seen in human alcoholics (Lewohl et al, 2011) and in other animal models of dependence Alcohol-responsive synaptic microRNAs and mRNAs D Most et al Nunez et al, 2013;Tapocik et al, 2013). We further identified microRNAs with overlapping patterns of expression that correlated with alcohol consumption.…”
Section: Discussionmentioning
confidence: 60%
“…Little is known about the microRNAs involved in the regulation of synaptic mRNA translation during alcohol dependence. Studies investigating the effects of chronic alcohol consumption in standard tissue (total homogenate, TH) preparations found a persistent change in the expression of microRNAs and their target mRNAs in humans, mice, and rats (Lewohl et al, 2011;Gorini et al, 2013;Nunez et al, 2013;Tapocik et al, 2013). However, the standard TH preparation likely underestimates the number and magnitude of alcoholresponsive transcripts localized in the synapse (Lewohl et al, 2011;Most et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in this regard support this notion. For instance, a recent study in rats examining the effects of olanzapine on genome-wide DNA methylation in the hippocampus and cerebellum showed that widespread and tissue-specific changes in genome-wide methylation could mediate the activity of olanzapine while treating schizophrenia [93] . These examples raise the possibility that the mechanisms of action of certain approved drugs may involve previously uncharacterized epigenetic processes.…”
Section: Epigenetic Drug Targeting Dna Methylationmentioning
confidence: 99%